Efficient 2T CsKPb(IBr)3—Tin Incorporated Narrow Bandgap Perovskite Tandem Solar Cells: A Numerical Study with Current Matching Conditions. Issue 11 (7th October 2021) - Karthick, Sekar; Nwakanma, Onyekachi Michael; Mercyrani, Babudurai; Bouclé, Johann; Velumani, Subramaniam
Abstract: This study numerically investigates a highly efficient tandem‐structured C s K P b ( I B r ) 3 − F A C s P b S n I 3, F A M A S n G e I 3, and M A P b S n I 3, perovskite‐perovskite model solar cells using the solar cell simulator capacitance software ( S C A P S − 1 D ), consisting of wide‐bandgap top potassium incorporated inorganic cesium‐based perovskite cell ( C s K P b ( I B r ) 3 − 1.92 eV ) and narrow‐bandgap bottom tin incorporated perovskite cells ( F A C s P b S n I 3 − 1.29 eV, F A M A S n G e I 3 − 1.40 eV, and M A P b S n I 3 − 1.16 eV ). The study explores and optimizes the front and rear perovskite absorber layer parameters (especially thickness) and current matching conditions ideal for tandem device performance. The simulated top standalone inorganic solar cell parameters yield a power conversion efficiency of over 13% (for all models), while the bottom perovskite devices simulated with filtered spectrum yield an efficiency of 14.17% for F A C s P b S n I 3, 8.54% for F A M A S n G e I 3, and 13.30% for M A P b S n I 3, respectively. The study and quantification of the current matching points for the tandem configuration provide some insight into the device's performance, which is beneficial for its efficiency enhancement. The resultant simulated optimized tandem cells offer a maximum efficiency of 21% for C s K P b ( I B r ) 3 − F A C s P b S n I 3 model, 17.5% for C s K P b ( I B r ) 3 − F A M A S n G e I 3 model, and 20% for C s K P b ( I B r ) 3 − M A P b S n I 3 model, respectively, with improved parameters. Abstract : A systematic SCAPS‐1D simulation study is performed by adopting the perovskite‐perovskite (i.e., CsKPb(IBr)3 – FACsPbSnI 3, FAMASnGeI 3, MAPbSnI 3 ) tandem solar cell models. The optimized standalone top and bottom sub‐cell conditions combined in 2T monolithic tandem models with the appropriate current matching conditions using filtered transmitted spectrum provide the efficiency of 21%, 17.5%, and 20% for FACsPbSnI 3, FAMASnGeI 3, and MAPbSnI 3 devices, respectively.